Methods used to measure postural balance - Ewelina Stefania Pankanin; Paulina Miętkowska (Kazimierz Wielki University, 2018)
Balance is one of the basic motor skills of a man. It is essential for the proper functioning of a human being, and every deviation from the norm strictly affects the quality of life. For the maintenance of the vertical position of the body it is a responsible interaction: the organ of balance, the sense organ of deep feeling, the organ of vision. The complex structure of the balance system requires appropriate research tools. Research techniques can be divided into: balance tests, instrumental techniques and system / physiological assessment. There is no single, universal research technique, so choosing the right tool should be dictated by individual research needs.